A Framework for Enhancing Performance and Minimizing Automation Testing Cost and Time Using Efficient Methods - Kaur, Tavleen (My University, 2015)
Software Testing is an important part of software development process. The aim of software testing is to find bugs and errors in the software. It also ensures that actual results are matching with the expected results and the requirements specified by the customer are being satisfied by the software developed. Software testing also tests the software for factors like efficiency, performance, response time, compatibility, security, reliability etc., and hence, ensures the quality of the software. In recent times, the technology has advanced to a larger extent, which in turn, has led the industries to require much complex and riskier software/applications, which also requires improvement in quality of software. So for this reason, to find the maximum bugs in software in lesser time, many organizations have adopted the technique of Test Automation. There is always some cost involved in everything. Testing and maintenance costs are approx. more than 50% of total cost of software development. If chosen the wrong methods and process for test automation, it can lead to 70-80% of total cost of software development, which could be out of the budget and efforts and time will also be wasted. So, the tester must ensure that the methodologies, process and framework used for the automation are the best and efficient enough so as to reduce the costs and increase the performance. The work that has been carried out in this thesis is focused on the implementation of some of the efficient methods and the framework, which can help in achieving the above stated purpose to a great extent. Following the correct process in the early and initial phase of the testing can help in cutting down the cost, efforts and time and increasing the performance of test automation.
ME, CSED
Keywords: Automation; HPQTP; OATS; OpenScript; Testing Tool; Framework; Bug Prone; CSED